2018
DOI: 10.3847/1538-4357/aaceaa
|View full text |Cite
|
Sign up to set email alerts
|

Energy Deposition by Energetic Electrons in a Diffusive Collisional Transport Model

Abstract: A considerable fraction of the energy in a solar flare is released as suprathermal electrons; such electrons play a major role in energy deposition in the ambient atmosphere and hence the atmospheric response to flare heating. Historically the transport of these particles has been approximated through a deterministic approach in which first-order secular energy loss to electrons in the ambient target is treated as the dominant effect, with second-order diffusive terms (in both energy and angle) being generally… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Such a non-local flux could effectively carry energy to the footpoints of the loop (Karpen & DeVore 1987), providing an additional source of heat that can lead to thermal instabilities, which requires further examination. It has also been suggested that the diffusion of non-thermal elec-trons to greater depths than predicted by the cold thick-target model is non-negligible (Emslie et al 2018;Jeffrey et al 2019). While this diffusion would allow energy to penetrate further shortly after the onset of heating, it is still not clear that the beam itself would last long enough to induce TNE (the heating needs to be on the order of the cooling time, Johnston et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a non-local flux could effectively carry energy to the footpoints of the loop (Karpen & DeVore 1987), providing an additional source of heat that can lead to thermal instabilities, which requires further examination. It has also been suggested that the diffusion of non-thermal elec-trons to greater depths than predicted by the cold thick-target model is non-negligible (Emslie et al 2018;Jeffrey et al 2019). While this diffusion would allow energy to penetrate further shortly after the onset of heating, it is still not clear that the beam itself would last long enough to induce TNE (the heating needs to be on the order of the cooling time, Johnston et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Electron beam heating has been previously implemented in HYDRAD (Reep et al 2013. We use the heating function derived by Emslie (1978), though a recent study suggested a modification to this to include the effect of diffusion in pitch angle, which effectively decreases the height at which electrons deposit their energy (Emslie et al 2018). In this work, we assume an injected electron flux spectrum with a sharp low-energy cut-off:…”
Section: Electron Beamsmentioning
confidence: 99%
“…Battaglia et al (2012) used a stochastic differential equation approach to model the source sizes of X-rays produced by nonthermal electrons injected at the top of loop models. Emslie et al (2018) used a collisional transport model to consider the effects of momentum and pitch-angle diffusion on the energy deposition rate from nonthermal electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Analytic fast electron models aim to estimate the change of the fast electron energy and pitch angle owing to collisions via analytic means, where it is assumed that these electrons are moving along magnetic field lines. Two types of models are often used in solar physics, one based on the solution of the Boltzmann equation with a Fokker-Planck treatment of collisions (McTiernan & Petrosian 1990;Allred et al 2015;Kerr et al 2016;Brown et al 2018;Emslie et al 2018), the other based on analytic energy loss rates of test electron beams in cold target plasma using a scattering treatment (Brown 1972;Emslie 1978). Analytic fast electron models, together with one dimensional (1D) (M)HD models, have been widely used to study the generation of evaporation of chromospheric plasma due to energetic electron deposition (e.g.…”
Section: Introductionmentioning
confidence: 99%